The Impact of Road Connection on Employment and Education in Northern Canada - Stringer, Thomas; Joanis, Marcelin (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
Road connection is viewed as a contributing factor to a variety of positive economic outcomes. However, for remote subarctic communities, it can also mean a significant impact on in their way of life. To which extent does road connection impact socio-economic outcomes such as salary, education or employment? This paper uses census data from Northern Quebec and Labrador to assess the effects of road connection on municipalities connected between 1986 and 2016. Using a difference-in-differences specification to an OLS regression model, assorted with robustness checks, we find that road connection is correlated with increased employment rates and educational attainment and decreased unemployment. While we also find positive and significant correlations between road connection and income in many specifications, that particular result is not robust when ensuring that error terms are not subject to cross-sectional dependence. Overall, our results support the conjecture that road connection of remote municipalities generates non-negligible economic benefits.